Hubungan Karakteristik Pasien Diabetes Melitus Tipe 2 dengan Komorbid Hipertensi terhadap Kepatuhan Minum Obat Menggunakan MARS-5: The Relationship Between the Characteristics of Type 2 Diabetes Mellitus Patients with Comorbid Hypertension on Medication Adherence using MARS-5 - Dian Oktianti; Sikni Karminingtyas (Universitas Ngudi Waluyo, 2024)
Diabetes mellitus is a group of metabolic disorders characterized by hyperglycemia and abnormalities in carbohydrate, fat and protein metabolism. Diabetes mellitus treatment requires a long period of time, so patients are expected to be compliant in taking medication. High adherence to medication can reduce complications of diabetes mellitus. The aim of the study was to determine the relationship between the characteristics of type 2 diabetes mellitus patients who have comorbid hypertension and patient compliance in taking antihypertensive medication. This research is a non-experimental quantitative research with a cross sectional design. The research sample was type 2 diabetes mellitus sufferers with hypertension who received an antihypertensive therapy regimen. The sampling technique used convenience sampling and a total sample of 79 patients was obtained. Adherence to taking antihypertensive medication was measured using the Medication Adherence Report Scale-5 (MARS-5) questionnaire. Univariate data analysis to describe patient characteristics and bivariate analysis to determine the relationship between patient characteristics and compliance levels using the Chi square test with a confidence level of 95%. The results showed that the level of compliance with taking antihypertensive medication based on the MARS-5 questionnaire was 30 patients (37.97%) classified as high and 49 patients (62.03%) classified as low with a mean MARS-5 value of 23.06 ± 2.14. There was a relationship between patient characteristics and the level of adherence to taking antihypertensive medication with significant value more than 0.05 (gender p= 0.974; age p= 0.757; education level p= 1.000). ABSTRAK Diabetes melitus merupakan penyakit kronis yang ditandai dengan meningkatnya kadar gula darah melebihi nilai normal. Pengobatan diabetes melitus membutuhkan jangka waktu lama, sehingga pasien diharapkan patuh dalam minum obat. Kepatuhan minum obat yang tinggi dapat menurunkan penyakit komplikasi diabetes melitus. Penelitian ini bertujuan mengetahui hubungan karakteristik pasien diabetes melitus tipe 2 yang mempunyai komorbid hipertensi terhadap kepatuhan pasien dalam meminum obat antihipertensi. Penelitian ini termasuk penelitian kuantitatif non eksperimental menggunakan rancangan cross sectional. Sampel dalam penelitian yaitu penderita diabetes melitus tipe 2 dengan hipertensi yang mendapatkan regimen terapi antihipertensi. Teknik sampling menggunakan convenience sampling dan didapatkan total sampel 79 pasien. Kepatuhan minum obat antihipertensi diketahui dengan kuesioner Medication Adherence Report Scale-5 (MARS-5). Data dianalisa secara univariat untuk menggambarkan karakteristik pasien, analisis bivariat untuk mengetahui hubungan karakteristik pasien dengan tingkat kepatuhan menggunakan uji chi square dengan taraf kepercayaan 95%. Penelitian memperlihatkan tingkat kepatuhan minum obat antihipertensi berdasarkan kuesioner MARS-5 sebanyak 30 pasien (37,97%) tergolong tinggi dan 49 pasien (62,03%) tergolong rendah dengan rerata nilai MARS-5 yaitu 23,06 ± 2,14. Terdapat hubungan antara karakteristik pasien dengan tingkat kepatuhan minum obat antihipertensi dengan nilai signifikansi lebih dari 0,05 (jenis kelamin p= 0,974; usia p= 0,757; tingkat pendidikan p= 1,000).